An Experimental Study Of Scientific Aproach Combined With CIRC Technique On Eighth Grade Students Writing Competency At SMP Harapan Nusantara Viewed From Text Type - ., NI WAYAN MEI INDRAYANI; ., PROF. DR. DEWA KOMANG TANTRA, M.Sc.; ., DR. NI MADE RATMININGSIH, M.A. (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2016)
This study aimed at : a) investigating the significant effect in writing competency the between students who were treated by using scientific approach combined with CIRC technique and those who were treated by using scientific approach combined with conventional strategy viewed from text types, b) students who were treated by using scientific approach combined with CIRC technique and those who were treated by using scientific approach combined with conventional strategy across descriptive paragraph, c) students who were treated by using scientific approach combined with CIRC technique and those who were treated by using scientific approach combined with conventional strategy across narrative paragraph. This study was an experimental study recruiting 353 students as the sample of the research. Post-test only control group design was applied as the research design. Post test was administered to discover the impact of the treatment. The data obtained from the post test were analyzed by using descriptive and inferential statistic analysis. Through the descriptive analysis, it was found that the mean score of the group were who were taught by using scientific approach combined with CIRC technique was higher than those who were taught by using scientific approach combined with conventional strategy viewed from text types. It means that the students who were treated by using scientific approach combined with CIRC technique is better than those who were treated by using scientific approach combined with conventional strategy viewed from text types, students who were treated by using scientific approach combined with CIRC technique is better than those who were treated by using scientific approach combined with conventional strategy across descriptive , students who were treated by using scientific approach combined with CIRC technique is not better than those who were treated by using scientific approach combined with conventional strategy narrative paragraph. These findings provide empirical evidence of the importance to determine teaching strategies taught in reading classes. Kata Kunci : Writing Competency, Scientific Approach, CIRC Technique, Text Types Penelitian ini bertujuan untuk mencari pengaruh signifikan diantara a) siswa pemahaman membaca siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan teknik CIRC dan siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan strategi konvensional dilihat dari jenis teks; b) siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan teknik CIRC dan siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan strategi konvensional di teks descriptive c) siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan teknik CIRC dan siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan strategi konvensional di teks narrative. Sampel penelitian berjumblah 353 siswa kelas 8 SMP Harapan Nusantara pada tahun ajaran 2015/2016. Post-Test Only Control group diaplikasikan sebagai desain penelitian. Setelah sesi perlakuan, post test diberikan untuk mengetahui pengaruh data yang diperoleh melalui post-test dianalisis secara deskriptif dan inferential. Secara deskriptif diketahui bahwa, siswa yang mengikuti pengajaran pendekatan ilmiah kombinasi dengan teknik CIRC lebih tinggi skornya daripada siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan strategi konvensional dilihat dari pemahaman membaca pada jenis teks; kedua siswa yang mengikuti pengajaran pendekatan ilmiah kombinasi dengan teknik CIRC lebih baik daripada siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan strategi konvensional di teks deskripsi; ketiga siswa yang mengikuti pengajaran pendekatan ilmiah kombinasi dengan teknik CIRC tidak lebih baik daripada siswa yang diajar dengan pengajaran pendekatan ilmiah kombinasi dengan strategi konvensional di teks narrative. Temuan ini memberikan bukti empiris tentang pentingnya penggunaan strategi mengajar yang sesuai yang diajari dalam membaca. keyword : Kemampuan menulis, Pendekatan Ilmiah, teknik CIRC, dan Jenis Teks